2021
DOI: 10.3390/molecules26071893
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and Biocompatible Silatrane Polymers

Abstract: In this study, new biodegradable and biocompatible amphiphilic polymers were obtained by modifying the peripheral hydroxyl groups of branched polyethers and polyesters with organosilicon substituents. The structures of the synthesized polymers were confirmed by NMR and GPC. Organosilicon moieties of the polymers were formed by silatranes and trimethylsilyl blocks and displayed hydrophilic and hydrophobic properties, respectively. The effect of the ratio of hydrophilic to hydrophobic organosilicon structures on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The results obtained by Istratov et al indicated the possible creation of biodegradable and biocompatible amphiphilic polymers bearing the silatrane groups. It was found that APS-containing polymers ( 7 ) ( Figure 3 ) positively influence the germination of wheat, oat, and rye seeds (germination percentage, H 2 O—77%, germination percentage, ( 7 )—98%) [ 44 ].…”
Section: Silatranyl Physiologically Active Compoundsmentioning
confidence: 99%
“…The results obtained by Istratov et al indicated the possible creation of biodegradable and biocompatible amphiphilic polymers bearing the silatrane groups. It was found that APS-containing polymers ( 7 ) ( Figure 3 ) positively influence the germination of wheat, oat, and rye seeds (germination percentage, H 2 O—77%, germination percentage, ( 7 )—98%) [ 44 ].…”
Section: Silatranyl Physiologically Active Compoundsmentioning
confidence: 99%
“…It can also prevent biofilm formation or internal tissue damage due to the implant and the subsequent need for secondary surgery [17,18]. In a study [19], new biodegradable and biocompatible amphiphilic polymers were obtained by modifying polyesters with organosilicon substituents. Organosilicon fragments of polymers are formed by silatranes and exhibit hydrophilic and hydrophobic properties, respectively [20].…”
Section: Current Trendsmentioning
confidence: 99%
“…[14][15][16][17] Thus, the skeletons of I and II could supply the diverse electronic structures and have unique functionalities, such as superbase, [18][19][20] catalysis [21][22][23] and biological activity. [24][25][26][27] Alder and coworkers synthesized various derivatives of I and II and related species. 9,11,[28][29][30][31] 1,5-Diazabicyclo[3.3.3]undecane (1) 28 and 1,6-diazabicyclo [4.4.4]tetradecane (5) 29 are the typical examples.…”
Section: Introductionmentioning
confidence: 99%